An Analysis Of Diction In Maya Angelou’s Selected Poems - Ayuni, Nurfitri; Maghdalena, Maghdalena; Basa, Rowela (Journal of Language, Literature, and Educational Research, 2024)
Purpose of the study: This research aimed to find out what are the types of diction used by Maya Angelou in selected poems, they are “Still I rise”, “Touched by an angel” and “Equality” based on the theory of Abrams (1999) for analyzing the types of diction. There are four types of diction according to Abrams: concrete, abstract, denotation, and connotation. Methodology: This study uses a descriptive qualitative method with content analysis based on Abrams' theory (1999) to analyze diction in three poems by Maya Angelou: "Still I Rise," "Touched by an Angel,"* and "Equality."The procedure includes reading, identifying, classifying, and describing types of diction, such as concrete, abstract, denotation, and connotation. The main data are taken from the book “The Complete Collected Poems of Maya Angelou” (1994), with the researcher as the main instrument supported by data recording to ensure in-depth analysis. Main Findings: This research found concrete diction, abstract diction, denotative and connotative which are presented in seventy-nine (79) data from three poems. The researcher found 9 types of concrete diction, 21 types of abstract diction, 41 (forty-one) types of connotative and 8 (eight) types of denotative. Based on the data can be concluded that Maya Angelou mostly using connotative diction in selected poems. Novelty/Originality of this study: This research selects certain poems from Maya Angelou's work that have not been specifically analyzed in previous studies. By focusing on selected poems, this research can reveal nuances of diction that might be missed in a more general analysis.